Knowledge Sharing as a Mediator between Emotional Intelligence, Communication, and Employee Performance in the Agrotourism Sector - Syifa Emilia; Alfato Yusnar Kharismasyah (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2026)
Purpose: This study examines the effects of emotional intelligence and communication on employee performance, with knowledge sharing serving as a mediating variable in the agrotourism sector.Method: This study employs a quantitative approach using primary data collected through offline questionnaire distribution. A total of 152 employees of the PTPN IX Kaligua region participated as respondents. The data were analyzed using SEM-PLS with the support of SmartPLS version 4.Result: The findings indicate that emotional intelligence, communication, and knowledge sharing each have a significant positive effect on employee performance. Knowledge sharing mediates the relationship between communication and employee performance. However, knowledge sharing does not mediate the relationship between emotional intelligence and employee performance.Practical Implications for Economic Growth and Development: These findings highlight the importance of emotional intelligence, communication, and knowledge sharing in improving employee performance. Strengthening communication practices and fostering knowledge sharing among employees can enhance productivity, which may benefit organizational performance and, in the broader context, contribute to economic growth and development.Originality/Value: This study proposes a model that positions knowledge sharing as an intervening mechanism linking emotional intelligence and communication to employee performance in the agrotourism sector.